Neue Wege der Beschreibung von Rechtstermini: der semasiologisch-onomasiologische Ansatz der Begriffsbestimmung und seine Bedeutung für den Rechtsübersetzer - Wiesmann, Eva (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Within the framework of modern terminological findings, a new approach for the description of legal terms is presented which attempts to overcome the limitations posed by the traditional conceptual understanding of Wüster’s theory of terminology. The central question deals with the role of definition, which is of importance in the delimitation of legal terms, but more so and particularly in the formation of legal concepts. Viewed from the perspective of a modern conceptual understanding, legal concepts are the result, not the object of definition. Often, however , they may be formed through definitions only in the core area, but not in the marginal area important for the differentiation of legal concepts, and this means that further debate on the objects of law is required. By defining legal terms, and not legal concepts, a basic precondition is created for taking into consideration not only the subject specialist but also the linguistic context, and thus for fully taking into account the needs of the legal translator.